Re: CRTC PN 2010-623 : On Contributions by Broadcasting Distribution Undertakings to Local Expression - Rodgers, Guy (2010)

Association for Canadian Studies (ACS) and Quebec Community Groups Network (QCGN) Launch Canadian Diversity Issue Exploring Deep Diversity of English-speaking Quebec - Quebec Community Groups Network (QCGN) (2010)

ELAN Launches Recognizing Artists : Enfin Visibles! - English Language Arts Network (ELAN) (2010)

ELAN Speech to CRTC for Community TV Channel Hearing PN 2009-661 - Rodgers, Guy (2010)

Review of Key Documents on the English-language Film/TV/Media Production Industry in Quebec for the English-language Arts Network of Quebec - Magnetic North Associates (English-Language Arts Network (ELAN), 2010)
Responding to anecdotal evidence from their members, the Quebec chapters of ACTRA and DGC commissioned a major study of English-language production in Quebec based on CAVCO data (Appendix I). This 2008 report was titled “Going…Going…Gone: The Decline of English-language Production in Quebec 1996-7 to 2006-7”, and it demonstrated several long term trends in domestic production.
Keywords: Official Language Minority Community (OLMC)

Survey of the English-language Film/TV/Media Industry in Quebec for the English-language Arts Network of Quebec with funding from Telefilm Canada - Magnetic North Associates (English-Language Arts Network (ELAN), 2010)
There has been a significant shift in the demographic profile of the English-Quebec production industry since the last similar survey of English-Quebec producers in 2003. Today’s industry is more female, has fewer immigrants, and is much more bilingual. Sixty two per cent say they speak fluent French. This demographic shift may be caused by the departure of members of the industry with poorer French language skills or an increase in language skills.
Keywords: Official Language Minority Community (OLMC)

Re: CRTC 2009-661 : Review of Community Television Policy Framework - Rodgers, Guy (2010)

[Notes for a Speech from ELAN to CRTC at Hearing 2009-418] - Rodgers, Guy (2010)

ELAN Response to Questions Raised by the CRTC at the Community TV Hearing, April 30, 2010 - English Language Arts Network (ELAN) (2010)

What is Bill C-32? - English Language Arts Network (ELAN) (2010)
Bill C-32 is officially known as the Copyright Modernization Act. It was an attempt at a “Balanced Copyright” act introduced in Parliament on June 2, 2010, by the Conservative Party — Honourable Tony Clement, Minister of Industry, and the Honourable James Moore, Minister of Canadian Heritage and Official Languages. It contains changes to Canadian Copyright Law that are hotly contested by artists and authors of cultural media. The Bloc, NDP and Liberal parties are opposed to the act being passed in its current state, and are calling for amendments to be made.
Keywords: Official Language Minority Community (OLMC)